2016
DOI: 10.1016/j.bbr.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent social defeat alters N-methyl-d-aspartic acid receptor expression and impairs fear learning in adulthood

Abstract: Repeated social defeat of adolescent male rats results in adult mesocortical dopamine hypofunction, impaired working memory, and increased contextual anxiety-like behavior. Given the role of glutamate in dopamine regulation, cognition, and fear and anxiety, we investigated potential changes to N-methyl-D-aspartic acid (NMDA) receptors following adolescent social defeat. As both NMDA receptors and mesocortical dopamine are implicated in the expression and extinction of conditioned fear, a separate cohort of rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 99 publications
2
18
0
Order By: Relevance
“…Decreases in markers of glutamatergic signaling and dampened PFC excitability are also noted (Ishikawa et al, 2015; Novick et al, 2016; Ver Hoeve et al, 2014; Zhao et al, 2009). Given the requirement of NMDA receptor-mediated activity within PFC circuits during cognitive tasks (Arnsten & Rubia, 2012), this would presumably result in less recruitment of the PFC as required for effective top-down control.…”
Section: Impact Of Chronic Juvenile Stress On Prefrontal Cortex Anmentioning
confidence: 99%
“…Decreases in markers of glutamatergic signaling and dampened PFC excitability are also noted (Ishikawa et al, 2015; Novick et al, 2016; Ver Hoeve et al, 2014; Zhao et al, 2009). Given the requirement of NMDA receptor-mediated activity within PFC circuits during cognitive tasks (Arnsten & Rubia, 2012), this would presumably result in less recruitment of the PFC as required for effective top-down control.…”
Section: Impact Of Chronic Juvenile Stress On Prefrontal Cortex Anmentioning
confidence: 99%
“…In this respect, the goal of fear extinction learning is to retrain the brain to prevent the retrieval of aversive memories associated with the post-traumatic stress condition. However, the effectiveness of PET depends on multiple cellular mechanisms such as inflammation, neurotransmitter systems, and synaptic modifications in neural circuits associated with fear memory retrieval (Abraham et al, 2016; Novick et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Novick et al . () reported that repeated social defeat during adolescence produced long‐term changes in the expression of NMDA receptors in several brain areas (increases in the CA3 and decreases in the infralimbic PFC and central amygdala) but not in others (CA1, nucleus accumbens, caudate‐putamen, prelimbic and cingulate cortex, and basolateral amygdala). Finally, Stelly et al .…”
Section: Discussionmentioning
confidence: 99%
“…A single experience of defeat increased the ratio NMDA/AMPA binding in the CA3 area of the hippocampus (Krugers et al, 1993) and repeated episodic defeats enhanced the GluR1 AMPA subunit protein expression in the ventral tegmental area (VTA) . Furthermore, adolescent social defeat increased the NMDA receptor expression in CA3 in adulthood, although this expression decreased in the central amygdala and the infralimbic prefrontal cortex (PFC) (Novick et al, 2016). Sensitisation to the motor effects of amphetamine induced by the exposure to repeated social defeat was blocked by NMDA and metabotropic glutamate (mGlu5) receptor antagonists (Yap et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation